MDM2 for the practicing pathologist: a primer. Issue 5 (10th March 2023) - Menon, Aswathy Ashok; Deshpande, Vikram; Suster, David
Abstract : The mouse double minute 2 ( MDM2 ) gene is located on the long arm of chromosome 12 and is the primary negative regulator of p53. The MDM2 gene encodes an E3 ubiquitin–protein ligase that mediates the ubiquitination of p53, leading to its degradation. MDM2 enhances tumour formation by inactivating the p53 tumour suppressor protein. The MDM2 gene also has many p53-independent functions. Alterations of MDM2 may occur through various mechanisms and contribute to the pathogenesis of many human tumours and some non-neoplastic diseases. Detection of MDM2 amplification is used in the clinical practice setting to help diagnose multiple tumour types, including lipomatous neoplasms, low-grade osteosarcomas and intimal sarcoma, among others. It is generally a marker of adverse prognosis, and MDM2-targeted therapies are currently in clinical trials. This article provides a concise overview of the MDM2 gene and discusses practical diagnostic applications pertaining to human tumour biology.